Using ICF to Describe Problems With Functioning in Everyday Life for Children Who Completed Treatment for Brain Tumor: An Analysis Based on Professionals' Documentation - Björklund, Ann-Christin; Granlund, Mats; Santacroce, Sheila Judge; Enskär, Karin; Carlstein, Stefan; Björk, Maria (Frontiers in Rehabilitation Sciences, 2021)
Background: Children treated for braintumors often experience persistent problems affecting their activity performance and participation in everyday life, especially in school. Linking these problems to the ICF-CY classification system can be described as affecting body function, activity performance and/or participation. Services involved in the childs´everyday life have different focus and goals when meeting the child in context, which advantage the use of ICF-CY to overcome this impediment to follow-up and provide comprehensive support for braintumor treated children. The aim was to use the ICF-CY classification system to describe how professionals in health care, habilitation, and school document problems with everyday life functioning at body, activity and participation levels for children who ended braintumor treatment. Materials and Methods: A retrospective review of records from health care, habilitation and school concerning 9 children completed treatment for a brain tumor was implemented. Identified problems in everyday life were linked to ICF-CY codes. Descriptive statistics of ICF-CY linked code frequency supplemented by network visualization diagrams viewing the co-occurrence between codes within body, activity participation and environmental components were performed. Results: Most documented problems were found in health care records, whereas documentation in habilitation and school were sparse. The frequently occurring codes independent of record source, were linked to the body function component, ICF-CY linked problems in habilitation and school were salient in the activity and participation component. To gain a holistic picture of relations between ICF-CY codes/problems, network visualization diagrams was used to illustrate clusters of problems. Conclusion: Code prevalence likely reflects where healthcare professionals and educators focus their attention when meeting the needs of children treated for braintumor in context. To maximize the comprehensive view of children’s functioning and participation in everyday life, the full range of difficulties regarding body impairments, activity limitations and participation restrictions must be identified and linked to each other in patterns of co-occurrence, which the ICF-CY facilitate. However, ICF-CY provides no guidance how to identify networks of problems within body, activity, and participation. Identifying such networks are important for building comprehensive interventions for children.